2019
DOI: 10.9734/aprj/2019/v2i330045
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Phytochemical Content and Antioxidant Potential of Azadirachta indica and Parquetina nigrescens Leaves

Abstract: Aim: The aim of this study is to compare the phytochemical content and antioxidant potential of Azadirachta indica and Parquetina nigrescens leaves. Study Design: This study was made to fit a one way Analysis of Variance. Place and Duration of Study: This research was carried out in Premedical Science Department, Educational Advancement Centre, Ibadan and Pharmaceutical Laboratory of the University of Ibadan, Nigeria between January and June, 2018. Methodology: Both plants were harvested from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…The growing number of diabetics coupled with the harsh side effects of some synthetic drugs has led to the increasing search for alternatives which are relatively cheap with minimal side effects. Green leafy vegetables and fruits have been reported to have some health benefits [19,20]. Consequently, C. olitorius leaf is a green leafy vegetable popularly used as food and in traditional medicine for the management of some diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing number of diabetics coupled with the harsh side effects of some synthetic drugs has led to the increasing search for alternatives which are relatively cheap with minimal side effects. Green leafy vegetables and fruits have been reported to have some health benefits [19,20]. Consequently, C. olitorius leaf is a green leafy vegetable popularly used as food and in traditional medicine for the management of some diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23,24]. Most of the plants with hypoglycemic properties have been found to contain metabolites such as glycosides, alkaloid and flavonoids [19,20,25].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies has shown that a number of other plants and extracts have an antihyperglycemic and an insulin-stimulatory effect [24,31,32,33]. Most of these plants have been reported to be rich in phytochemicals and contain metabolites such as glycosides, alkaloid and flavonoids [29,30,34]. These metabolites could be responsible for the hypoglycemic effect of V. amygdalina leaves observed in this study.…”
Section: Discussionmentioning
confidence: 52%
“…The growing number of diabetes coupled with the harsh side effects of some synthetic drugs has led to the increasing search for alternatives which are relatively cheap with negligible side effects. Studies revealed that green leafy vegetables and fruits have some health benefits [29,30]. Thus, V. amygdalina leaf is a green leafy vegetable popularly used as food and in traditional medicine for the prevention and management of some diseases.…”
Section: Discussionmentioning
confidence: 99%
“…An antioxidant can be broadly defined as any substance that delays or inhibits oxidative damage to a target molecule. The major feature of an antioxidant is its ability to scavenge the free radicals due to their redox hydrogen donators and singlet oxygen quenchers [7,8].…”
Section: Introductionmentioning
confidence: 99%